Electrocatalytic Reduction and Voltammetric Determination of Metronidazole at Inlaying Ultra-Thin Carbon Paste Electrode - Zhan, Haihong; Qiao, Yuechun; Li, Quanmin (Asian Journal of Chemistry, 2015)
In this paper, nichrome was adopted as a substrate, to fabricate an inlaying ultra-thin carbon paste electrode (IUTCPE). Cyclic voltammetry and linear scan voltammetry were used to investigate the electrochemical responses of metronidazole. The results revealed that, in 0.1 mol L-1 Britton-Robinson buffer (pH 3), the inlaying ultra-thin carbon paste electrode showed a good electrocatalytic reduction towards metronidazole. Under optimized conditions, the well-defined reduction peak currents increased linearly with increasing the contents in the range of 7 × 10-7-1.17 × 10-3 mol/L. The detection limit (S/N = 3) was 2.8 × 10-7 mol/L. Inlaying ultra-thin carbon paste electrode has the advantages of simple procedure, good stability and low cost. The proposed method was successfully applied to metronidazole determination in tablets. The recovery was from 96.0 to 104.7 %.